Provision of Rewards and Punishments in Improving PAI Learning Outcomes at SMPN 2 Syamtalira Aron, Aceh - Buto, Zulfikar Ali; Taufiq, Taufiq; Safruddin, Safruddin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2022)
The learning delivered by Islamic Religious Education (PAI) Teachers often does not touch the motivation of students' learning, so that the learning process has not been able to improve learning outcomes as expected. This incident is not much different from that experienced by PAI teachers at Public Junior High School (SMPN) 2 Syamtalira Arun, which has an impact on poor learning outcomes due to the ability of PAI Teachers to encourage students to use punishment and reward methods that are in accordance with the conditions of their students. The research questions in this study are: 1) How is the implementation of the reward and punishment method to improve PAI learning outcomes? 2) What are the obstacles faced by PAI teachers? 3) How are the teachers' efforts in overcoming the existing obstacles? This type of research uses qualitative research with a phenomenological approach to the actual conditions of the research subject at the research location. Data collection techniques are carried out through observation, interviews, and documentation. Meanwhile, the data analysis techniques are data reduction, data presentation, and drawing conclusions. The provision of rewards and punishments in improving PAI learning outcomes at SMPN 2 Syamtalira Aron is carried out in various forms, for example, giving prizes and appreciation for those who excel and praise. Meanwhile, those who break the rules are given punishments that are educational both in groups and individually. The obstacles faced by PAI teachers in implementing rewards and punishments to improve PAI learning outcomes at SMPN 2 Syamtalira Aron are complex obstacles: 1) the students are mostly villagers, and most students are busy with activities to help their parents, 2) apathetic parents who do not want to know about their children's learning outcomes, 3) the obstacle is inadequate school facilities. The efforts made by PAI teachers in overcoming obstacles in implementing rewards and punishments to improve PAI learning outcomes at SMPN 2 Syamtalira Aron: 1) completing teaching administration, such as lesson plans, syllabus, media, and preparing learning materials; 2) activates the school MGMP (Subject Teachers Discussion).